Maternal thyroid function in different conditions of iodine nutrition in pregnant women exposed to mild-moderate iodine deficiency: an observational study - Moleti, Mariacarla; Di Bella, Beatrice; Giorgianni, Grazia; Mancuso, Alfredo; De Vivo, Antonio; Alibrandi, Angela; Trimarchi, Francesco; Vermiglio, Francesco (Clinical endocrinology (Oxford), 2011)
Summary Objective  We examined the effect of different conditions of nutritional iodine intake on maternal thyroid function throughout gestation in a cohort of healthy, anti‐thyroid antibody‐negative women from a mild‐moderately iodine‐deficient (ID) area. Design  Observational cohort study. Patients  The study included 168 women receiving prenatal preparations containing 150 μg of iodine from early pregnancy (150‐I group); 105 women who had regularly used (>2 years) iodized salt prior to becoming pregnant (I‐salt group); 160 women neither taking iodine supplements nor using iodized salt (no‐I group). Measurements  Maternal TSH, FT3 and FT4 were determined throughout gestation. Results  Mean TSH concentrations were higher among the 150‐I women than in the remaining two groups, and in a high proportion of them, TSH values were found to exceed the upper limit for gestational age. Conversely, the prevalence of low free‐thyroxine levels in the 150‐I women was similar to that observed in the I‐salt women and markedly lower than that recorded for the no‐I group. Conclusions  The regular use of iodine‐containing supplements proved effective in reducing the risk of inappropriately low FT4 levels during pregnancy. The observed TSH increase in 150‐I women may be because of a transient stunning effect on the thyroid gland, occurring as a result of the abrupt increase in daily iodine intake. Whilst the importance of gestational iodine supplementation is undisputed, we believe that in mild‐moderately ID areas, women considering conception should be advised to take iodine supplementation for several months prior to pregnancy.